Service Quality, Customer Satisfaction, Customer Trust, and Customer Loyalty in Service of Paediatric Polyclinic Over Private H Hospital of East Jakarta, Indonesia - Christian Elizar; Ratna Indrawati; Tantri Yanuar Rahmat Syah (Penerbit Kemala Indonesia, 2020)
Customer loyalty is considered as an important key to the success and profit of a hospital, so that a decrease in the number of visits from old patients or subscribed patients in the paediatric polyclinic of Private H Hospital is a serious problem. The purpose of this research is to determine the effect of service quality on customer loyalty with customer satisfaction and trust as an intervening variable in the services of a paediatric polyclinic in Private H Hospital. In this study, we used SEM method on 190 respondents to obtain the result. Here, the test results show has met the criteria of Goodness of Fit in which the t-value of service quality to customer satisfaction is 14.71, service quality to customer trust is 16.10, service quality to customer loyalty is 2.16, customer satisfaction to customer loyalty is 0.83, and customer trust to customer loyalty is 3.13. Customer trust significantly mediates the effect of service quality on customer loyalty while customer satisfaction cannot serve as a mediator since about 70% of patients at the paediatric polyclinic of Private H Hospital are National Health Insurance (JKN) members. By maintaining customer trust through the provision of services based on hospital accreditation standards and continuous evaluation, customer loyalty will increase as marked by the re-visit of patients even though there are other paediatric polyclinics offering more, even customers will recommend the paediatric polyclinic of Private H Hospital to other people.